Alterations of gut microbiota in patients with active pulmonary tuberculosis in China: a pilot study. (October 2021) - Shi, Wenpei; Hu, Yi; Ning, Zhu; Xia, Fan; Wu, Meiying; Hu, Yue O.O.; Chen, Cheng; Prast-Nielsen, Stefanie; Xu, Biao
Highlights: A reduced diversity of gut microbiota was observed in tuberculosis (TB) patients. TB patients had a low abundance of short-chain fatty acid-producing genera. Active TB patients showed a raised abundance of several conditional pathogens. Antibiotic use before TB diagnosis could alter the gut microbiota of patients. Abstract: Background: The aim of this study was to identify the differences in diversity, composition, and function of the gut microbiota between tuberculosis (TB) patients and healthy controls (HCs). Methods: A cross-sectional study was conducted in three cities of China. Stool samples from 94 treatment-naive TB patients and 62 HCs were analyzed by 16S rRNA gene sequencing. TB patients were further divided into antibiotic-free and antibiotic-exposure according to their use of non-specific antibiotics before the TB diagnosis. Results: Compared with HCs, antibiotic-free TB patients presented a different gut microbial community ( P < 0.005) and decreased Shannon diversity ( P < 0.005). Among TB patients, the relative abundances of short-chain fatty acid (SCFA)-producing genera such as Lachnospiraceae ND3007 group (log2(FC) = −2.74) were lower, while several conditional pathogen-related genera such as Enterococcus (log2(FC) = 12.05) and Rothia (log2(FC) = 6.322) were at higher levels. In addition, 41% of patients received antibiotics before TB diagnosis. Antibiotic exposure was correlated with an additional reduction in α diversity and depletion of SCFA-producing bacteria. Microbial functional analysis revealed that the biosynthesis capacity of amino acids and fatty acids was lower among TB patients compared to HCs. Conclusions: Significant alterations in gut microbiota composition and metabolic pathways of TB patients were observed. Antibiotic exposure could alter the gut microbiota of TB patients, which should be considered in anti-TB treatment.